Employee Performance: The Impact of Reward and Incentive: Study at Manufacturing Company - Elly Romy (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study sought to ascertain the impact of rewards and incentives for top-performing employees on employee morale at Manufacturing Company. The study population consisted of 180 employees at Manufacturing Company. The sample was selected using the random sampling approach. The sample size in this study consisted of 45 employees. This research falls under the category of quantitative research. Quantitative research focuses on measurable research objects and uses numerical or ratio-based variables to address specific problem formulations or test stated hypotheses. The multiple regression analysis yielded the equation Y = 5,263 + 0,422X1 + 0,447X2 + e, indicating that rewards and incentives had a statistically significant positive impact on staff morale. Concurrently, the outcomes of the test (t) or partial test indicate that awards favorably and favorably impact staff morale. Where is the value of tcount 3.286 visible? The t-table value of 2.01808 and the significance value of 0.002 indicate that the influence of the incentive variable on employee morale is positive and substantial. The t-count value of 3.693 further supports this finding. Similarly, the t-table value of 2.01808 and the significance value of 0.001 indicate a significant effect of the incentive variable on employee morale, with α set at 0.05. The coefficient of determination was determined to be 0.681. The independent variables, reward, and incentives, account for 68.1% of the variation in the employee morale variable. The remaining 31.9% is attributed to other variables not included in the model.